2019
DOI: 10.1002/cne.24815
|View full text |Cite
|
Sign up to set email alerts
|

Neuron types in the zebrafish optic tectum labeled by an id2b transgene

Abstract: The larval zebrafish optic tectum has emerged as a prominent model for understanding how neural circuits control visually guided behaviors. Further advances in this area will require tools to monitor and manipulate tectal neurons with cell type specificity. Here, we characterize the morphology and neurotransmitter phenotype of tectal neurons labeled by an id2b:gal4 transgene. Whole‐brain imaging of stable transgenic id2b:gal4 larvae revealed labeling in a subset of neurons in optic tectum, cerebellum, and hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 64 publications
(141 reference statements)
9
44
0
Order By: Relevance
“…Noticeably, a particular class of retinal ganglion cells shows bistratified axonal projections that reach both the SFGS6 and SGC (Robles et al, 2014). These results match with the distribution of the dendritic fields of type X cells described for the zebrafish adult (present results) and larva (DeMarco et al, 2019). Therefore, it seems that zebrafish type X cells probably receive direct retinal information, among other types of inputs.…”
Section: Reciprocal Toro-tectal Connectionssupporting
confidence: 91%
See 3 more Smart Citations
“…Noticeably, a particular class of retinal ganglion cells shows bistratified axonal projections that reach both the SFGS6 and SGC (Robles et al, 2014). These results match with the distribution of the dendritic fields of type X cells described for the zebrafish adult (present results) and larva (DeMarco et al, 2019). Therefore, it seems that zebrafish type X cells probably receive direct retinal information, among other types of inputs.…”
Section: Reciprocal Toro-tectal Connectionssupporting
confidence: 91%
“…These neurons showed a clear bistratified dendritic lamination in the SGC and the SFGS, which roughly coincides with the morphology of the type X tectal cells described after Golgi staining in the goldfish (Meek and Schellart, 1978). A recent study in zebrafish larva has shown that type X cells are labeled by id2b transgene, being able to observe the axon running along TL (DeMarco et al, 2019). In the carp tectum, the toropetal cells reported with retrograde labeling (Ito et al, 2003) appear to be more heterogeneous in appearance and location than those reported here in zebrafish, with cells located in the SFGS, SGC and SAC (Ito et al, 2003;present results).…”
Section: Reciprocal Toro-tectal Connectionssupporting
confidence: 81%
See 2 more Smart Citations
“…id2b:gal4 BAC transgene(DeMarco, Xu, Baier, & Robles, 2019): Tg (id2b:gal4) × Tg(UAS:GCaMP6s). Visual stimuli were presented to a single eye via an OLED screen equipped with magenta filters to minimize interference with GCaMP6s fluorescence detection(Figure 1a,b).…”
mentioning
confidence: 99%